Analisis Musicscape terhadap Kepuasan Konsumen di Parewa Coffee Bandar Purus Padang - Rahmat Mulia Qodri; Nidia Wulansari (Jurnal Manajemen Pariwisata dan Perhotelan, 2025)
This research is motivated by musicscape that affects consumer satisfaction at Parewa Coffee Bandar Purus Padang. This study aims to analyze musicscape on consumer satisfaction visiting Parewa Coffee Bandar Purus Padang. This type of research uses quantitative research with a causal associative approach method. The population in this study were consumers visiting Parewa Coffee Bandar Purus Padang with a sample of 117 consumers. The data collection technique used a google form questionnaire distributed via bar code scans that had been tested for validity and reliability. The data analysis used was the normality test, homogeneity test, and linearity test. Hypothesis testing used a simple linear test using SPSS. The results of this study found that musicscape was classified as good with a tcr result of 67.33%. For the consumer satisfaction variable, it was classified as good with a tcr result of 67.57%. Based on the results of the simple regression analysis test, the F count was 165.399 with a sig of 0.000, a regression coefficient of 0.365 with a sig value. 0.000. The R Square value is 0.590, meaning that the musicscape variable has a 59% effect on consumer satisfaction and 41% is influenced by other variables not examined in this study. This study provides insights to Parewa Coffee’s managementon the importance of musicscape optimazition to enhance consumer satisfaction. Additionally , the findings are expected to serve as a refrence for similar future studies and contribute to development of the coffee shop industry by maximizing the roleof music elements